2018
DOI: 10.1371/journal.pone.0191888
|View full text |Cite
|
Sign up to set email alerts
|

Why do people donate to conservation? Insights from a ‘real world’ campaign

Abstract: Non-governmental organisations (NGOs) play a key role in biodiversity conservation. The majority of these organisations rely on public donations to fund their activities, and therefore fundraising success is a determinant of conservation outcomes. In spite of this integral relationship, the key principals for fundraising success in conservation are still guided by expert opinion and anecdotal evidence, with very few quantitative studies in the literature. Here we assessed the behaviour of monetary donors acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 50 publications
2
36
1
Order By: Relevance
“…a stonefly) (Thomas-Walters and Raihani 2017; Veríssimo et al 2017). However, it is worth noting that contrary to this evidence, in an analysis of an offline large-scale fundraising campaign no effect of appeal or familiarity of species was found on monetary donations (Veríssimo et al 2018). These differences in results may be due to differences in methods, limiting comparability.…”
Section: The Species Effect -Aesthetics Anthropomorphism and Charismacontrasting
confidence: 71%
See 3 more Smart Citations
“…a stonefly) (Thomas-Walters and Raihani 2017; Veríssimo et al 2017). However, it is worth noting that contrary to this evidence, in an analysis of an offline large-scale fundraising campaign no effect of appeal or familiarity of species was found on monetary donations (Veríssimo et al 2018). These differences in results may be due to differences in methods, limiting comparability.…”
Section: The Species Effect -Aesthetics Anthropomorphism and Charismacontrasting
confidence: 71%
“…Much of the research and discussion in this area so far has centred on the efficacy of different narratives and contextual effects. This has included work on framing of messages, messenger effects, and emotionalisation, integrating research from fields such as human wildlife conflict, science communication, and environmental education (Larson 2005;Draheim et al 2011;Flemming et al 2018;Veríssimo et al 2018). However, despite the adage ''a picture is worth a 1000 words'', there has been less investigation into the potential impacts of visual representations of wildlife.…”
Section: And the Society For Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is mixed evidence about the association between ‘patriotic’ values or ethnocentrism and donation behaviour. More specifically, some authors have found donors to prefer local conservation causes (Dallimer et al ., ; Cárdenas & Lew, ), whereas others have found no evidence (Veríssimo et al ., ).…”
Section: Introductionmentioning
confidence: 97%